Terrestrial Radio Broadcasting in the Face of Challenges of the Digital Era - Skrzypczak, Jędrzej (Media - Culture - Social Communication, 2019)
The process of digitization of terrestrial radio broadcasting in Poland has provoked much controversy. DAB+ offers easier, (ultimately) cheaper and clear reception without interference, lower transmission costs (except a simulcast), energy savings (digital transmitters require less power) and, finally, a wide variety of programs. Critics emphasize that digital radio of the DAB+ standard is not as attractive for listeners as audio broadcasting available on the Internet and it is connected with huge costs for broadcasters, listeners and the state and can pose a threat to the current market position of commercial broadcasters. DAB/DAB+ is an alternative to AM/FM and not to webcasting. Certainly, appropriate impetus for regulations at the European Union level could support the development of this new technology. It is necessary to adopt a national strategy to implement digital radio broadcasting and an act on digitization that will cover issues of digital conversion.